Transcriptome Analysis Reveals the Molecular Mechanism of Grape Inflorescence Elongation after Applying Microbial Fertilizers - Qiufeng Huang; Guopin Chen; Shuyu Xie; Wei Li; Jing Huang; Yu Huang; Jingxi Guan; Muming Cao (Journal of the American Society for Horticultural Science, 2023)
Microbial fertilizers can activate and promote nutrient absorption and help inflorescence elongation. To understand the molecular mechanisms governing grape (Vitis vinifera) inflorescence elongation after microbial fertilizer application, we comprehensively analyzed the transcriptome dynamics of ‘Summer Black’ grape inflorescence at different leaf stages. With the development of ‘Summer Black’ grape inflorescence, gibberellic acid content gradually increased and was clearly higher in the microbial fertilizer group than in the corresponding control group. In addition, the microbial fertilizer and control groups had 291, 487, 490, 287, and 323 differentially expressed genes (DEGs) at the 4-, 6-, 8-, 10-, and 12-leaf stages, respectively. Kyoto Encyclopedia of Genes and Genomes pathway annotation revealed that most upregulated DEGs were enriched in starch and sucrose metabolism pathways at the 6-, 8-, and 10-leaf stages. Weighted gene coexpression network analysis identified stage-specific expression of most DEGs. In addition, multiple transcription factors and phytohormone signaling-related genes were found at different leaf stages, including basic helix-loop-helix proteins, CCCH zinc finger proteins, gibberellin receptor GID1A, 2-glycosyl hydrolases family 16, protein TIFY, MYB transcription factors, WRKY transcription factors, and ethylene response factor, suggesting that many transcription factors play important roles in inflorescence elongation at different developmental stages. These results provide valuable insights into the dynamic transcriptomic changes of inflorescence elongation at different leaf stages.